Effective treatment of severe acute pancreatitis and COVID-19 pneumonia with tocilizumab - Piotr Zielecki; Magdalena Kaniewska; Mariusz Furmanek; Tomasz Bulski; Grażyna Rydzewska (Gastroenterology Review)
In December 2019 the coronavirus disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) was reported for the first time in Wuhan, China [1], and it subsequently rapidly spread to the rest of the world. On 11th March 2020 COVID-19 was declared a pandemic by the World Health Organisation [2]. The most common symptoms are fever, cough, shortness of breath, fatigue, myalgia, and loss of smell and taste [3], but gastrointestinal symptoms like vomiting, diarrhoea, and abdominal pain are also reported [4, 5]. SARS-CoV-2 uses angiotensin-converting enzyme (ACE) 2 as an entry receptor to infect host cells [6]. The highest ACE 2 expression was found in alveolar cells of the lungs [7], but also in the heart, kidneys, and gastrointestinal tract, including the pancreas. To date, it is not known if SARS-CoV-2 can cause pancreatic cell damage leading to acute pancreatitis, but in many cases serum lipase and amylase levels are elevated [8]. A study also showed that patients with history of acute pancreatitis may be more susceptible to COVID-19, but the mechanism of this phenomenon is not known yet [9]. Many severe COVID-19 patients develop acute respiratory distress syndrome (ARDS), which is the most serious complication of SARS-CoV-2 infection [10]. It has been reported that a systemic inflammatory syndrome called cytokine release syndrome (CRS) is responsible for the development of ARDS in SARS-CoV-2 infection, which leads to pulmonary fibrosis and organ failure. In this pathophysiological process interleukin-6 (IL-6), and B and T cells play key roles [11]. Tocilizumab (TCZ) is a monoclonal antibody that competitively inhibits the binding of IL-6 to its receptor (IL-6R). This mechanism blocks receptor complex signal transduction to inflammatory mediators responsible for B and T cell activation and inhibits cytokine storm [12]. IL-6 pathway blocking can be a new method for the treatment of severe COVID-19 patients [13], and tocilizumab is expected to become an effective drug against COVID-19, but currently scientific data are limited. One study showed that TCZ might reduce mortality in patients with severe COVID-19 pneumonia [14], but to date there have been no human studies evaluating tocilizumab in the treatment of acute pancreatitis. U.S. Food and Drug Association (FDA)-approved phase III randomised controlled trials on tocilizumab are ongoing [15]. We report the first (to date) case study of a patient with severe acute pancreatitis and COVID-19 pneumonia treated effectively with tocilizumab.